DEFINING THE URBAN DEVELOPMENT STRATEGY IN THE REPUBLIC OF SERBIA - Stojanovic, Katarina; Vojnović, Boško; Vladimirović, Ivana (Journal of process management and new technologies, 2019)
It is not possible to distinguish urban development from the context of comprehensive development. This work proves it. The first part analyzes the systemic and strategic approach in the classical approach, while in the second part it formulates recommendations for the selection of strategies, as well as the strategies themselves in the context of urban development in the Republic of Serbia.